Visible Light Photoelectrochemical Properties of PbCrO4, Pb2CrO5, and Pb5CrO8 - Lee, Heung Chan; Cho, Sung Ki; Park, Hyun S.; Nam, Ki Min; Bard, Allen J. (American Chemical Society, 2017)
Photoactivities of lead chromates with various combinations of Pb and Cr are rapidly screened using scanning electrochemical microscopy (SECM): In the rapid screening investigation, the metal oxide spot electrode With a Pb/Cr ratio of 2:1 exhibits the highest photoactivity among the semiconductor prepared with different compositions. The pliotoadtivity electtoChemical properties. of electrodes of PbCrO4; Pb(2)crO(5), and Pb(5)crO(8) are further studied following the combinatorial screening. In the bulk electrode measurements, the Pb2CrO5 bulk electrode displays the highest photocutrent of 0.23 mA/cm(2) for SO32- oxidation at 0.4 V vs Ag/Agcl under 100 mW/cm(2) UV vis light irradiation. Pb2CrO5- presents visible, light activity with an absorption wavelength up to 550 nm and an incident photon to current conversion efficiency (IPCE) of 10% at the wavelength of 340 nm. The onset wavelength observed in the UV vis absorption spectrum increases with increasing Pb contents in lead chromates. Optically obtained direct band gaps decreased from 2.38 to 2.26 to 2.07 eV for PbCrO4, Pb2CrO5, and Pb5CrO8, respectively. However, the onset wavelength that appeared in IPCE is 2.26 +/- 0.02 eV for all three lead chromates where the photocurrent under longer wavelength light irtacliatinn is insignificant. The results imply that more Pb 6s orbitals form interband states, increasing optical transitions in lead chromates. The band structures of PbCrO4, Pb2CrO5, and Pb5CrO8 are also determined by electrochemical analyses and ultraviolet photoelectron spectroscopy (UPS).
Keywords: SCANNING ELECTROCHEMICAL MICROSCOPY; WATER OXIDATION; OPTICAL-PROPERTIES; PHOTOCATALYSTS; HYDROGEN; FILM; PHOTOCONDUCTIVITY; PHOTOANODES; BEHAVIOR; DOPANTS